Constructing a profound experience model of Chinese Intangible Cultural Heritage Tourism based on grounded theory - Ming Lou; Shaomei Hu; Di Hu; Qing Zhang (PLoS ONE, 2026)
The purpose of this paper is to understand the generative mechanism of the profound experience in Chinese Intangible Cultural Heritage (ICH) tourism and its construction of meaning, to enrich the research on cultural tourism experiences, and to provide theoretical support for the sustainable development of Chinese ICH tourism. The study employs a Grounded Theory approach to summarize the theoretical model of profound experiences in Chinese ICH tourism, based on the network text descriptions of typical profound experiences in Chinese ICH tourism. The results of the study indicate that:(1) The theoretical model of profound experience in Chinese ICH tourism consists of four main categories: basic conditions, perceptual evaluation, personal significance, and social significance, along with 15 corresponding subcategories. (2) Professional service touchpoints, experience content innovation, scene atmosphere creation, application of modern technology, participation in interactive socialization are the basic conditions for the generation of profound experiences in ICH tourism. The dimensions of perceptual evaluation, such as sense of participation, sense of wonder, sense of immersion, sense of resonance, and sense of value, can describe the profound experiences obtained by tourists. Cultural cognition, cultural identity, and cultural memory reflect the personal significance achieved through the profound experience of ICH tourism, while the inheritance and dissemination of ICH reflect its social significance. The findings of this paper highlight the importance of profound experiences in enhancing the quality of cultural tourism and offer insights to Chinese tourist attractions, assisting them in improving tourism design in aspects such as tourism products, service systems, and scenarios, thereby elevating the overall experience quality of ICH tourism.